Approximative K-atomic decompositions and frames in Banach spaces. Issue 1 (5th April 2018) - Jahan, Shah
Abstract : L. Gǎvruţa (2012) introduced a special kind of frames, named K -frames, where K is an operator, in Hilbert spaces, which is significant in frame theory and has many applications. In this paper, first of all, we have introduced the notion of approximative K -atomic decomposition in Banach spaces. We gave two characterizations regarding the existence of approximative K -atomic decompositions in Banach spaces. Also some results on the existence of approximative K -atomic decompositions are obtained. We discuss several methods to construct approximative K -atomic decomposition for Banach Spaces. Further, approximative  d -frame and approximative  d -Bessel sequence are introduced and studied. Two necessary conditions are given under which an approximative  d -Bessel sequence and approximative  d -frame give rise to a bounded operator with respect to which there is an approximative K -atomic decomposition. Example and counter example are provided to support our concept. Finally, a possible application is given.